Impact of the COVID-19 pandemic on the psychological status of undergraduate medical students in Saudi Arabia: A cross-sectional double-scale study. Issue 14 (7th April 2023) - Ewid, Mohammed; Amal, Yassien; Billah, Syed Muhammad Baqui; Kalou, Yazan; Zitoun, Osama A.; Alnaser, Adnan Raed; Nashawi, Mhd Oubai; Almazrou, Abdulrahman
Abstract : The COVID-19 pandemic is a major health care catastrophe that affects people's physical and mental well-being worldwide. Medical students are at an increased risk of mental health hazards during the COVID-19 pandemic. Sulaiman Al Rajhi University (SRU), the site of our study, is located in Qassim province in the Kingdom of Saudi Arabia. We conducted this study to assess the prevalence of depression, stress and anxiety symptoms among SRU medical students during the quarantine and while learning online shortly after the announcement of documented COVID-19 cases in Kingdom of Saudi Arabia. In this cross-sectional study, an online questionnaire was sent to all medical students of SRU; 278 students responded (71%). We collected participants' demographic, socioeconomic, and academic data. The Depression, Anxiety, and Stress scale and the Fear of COVID-19 Scale were used as the validated mental health assessment tools. Depression, anxiety and stress symptoms were found in 23%, 11%, and 6% of students, respectively. Females were more likely to have anxiety ( P = .03) than males. Students who had close contact with COVID-19 cases, those whose lives were affected by COVID-19, and those with poor socioeconomic status had significantly higher levels of stress, anxiety, and depression compared to their counterparts ( P = .004, .01, .01, respectively). Students from high-viral-load areas, unmarried students, and those who did not live with their families were more stressed ( P = .06, .01, .01, respectively). The Fear of COVID-19 Scale was positively correlated with all Depression, Anxiety, and Stress components (depression: r = 0.36, anxiety: r = 0.45, and stress: r = 0.39, P < .001 for all). Medical students, especially female students, are at an increased risk of developing depression, anxiety, and stress symptoms with increased COVID-19 fear during the pandemic. The study highlights the importance of mental health screening for female students, students of low socioeconomic status, and relatives of COVID-19 cases. Our findings could help institutions adjust mental health services in the future amid such pandemics.